Clitoria ternatea Flower Extract Inhibits Matrix Mettaloproteinase-3 leading to the promotion of α-SMA Gene Expression in UVB-Induced Rat Model - Muna, Nugraheni Itsnal; Amalina, Nur Dina; Husain, Sofian Azalia (International Journal of Cell and Biomedical Science, 2023)
This study aimed to determine the effect of administration of Clitorea ternatea flower extract (C. ternatea) in a gel on the expression of MMP-3 and α-SMA in the skin of rat models induced by UVB light exposure. This research design is experimental research with a post-test control group design. This study was divided into four treatment groups: a healthy group, a UVB-negative control, a 5% C. ternatea gel treatment group (T1), and a 10% C. ternatea gel treatment group (T2). Negative control, T1, and T2 control groups were given UVB treatment with 302 nm energy of 160 mJ/cm2 for 5 days. In the treatment groups T1 and T2 were given the gel of C. ternatea from the 6th day until the 14th day. On day 15, all treatment groups were terminated, and the expression of MMP-3 and α-SMA genes was analyzed using qRT-PCR. In the 10% C. ternatea gel treatment group, there was a decrease in MMP-3 gene expression (0.73±0.26) and an increase in α-SMA gene expression (16.4±8.3) compared to the UVB control group which had gene expression. MMP-3 (3.24+1.05) and α-SMA gene expression (0.1±0.0). The administration of C. ternatea gel resulted in a reduction in the expression of the MMP-3 gene and an increase in the expression of the α-SMA gene. Overall, C. ternatea has the potential to prevent UVB-induced hyperpigmentation.